A Critical Analysis of Pakistani National Press Portrayal of Zakat Advertisements during Ramadan - Muhammad Tarique; Dr Lubna Shaheen (Journal of Peace, Development and Communication, 2022)
Zakat is a religious alms-giving or welfare contribution among Muslims. The Zakat donors themselves have to decide to whom it should be given or direct deduction from the banks (in Pakistan). Zakat is the fourth of Islam’s five basic pillars, and it is collected during the Holy Month of Ramadan, just before Eid ul Fitr, the joyous festival at end of Ramadan. This research examines Zakat campaign during Ramadan in Pakistani leading press. The purpose is to analyse whether the specific images and symbols are spiritually drawn from established Islamic beliefs, or commercial with no religious connotation? Also, to analyse the appeals used in the process of persuasion. The results show that appeals e.g., physical disability, poverty, orphans and old age, which attract the readers and persuade them to contribute are used. But organizations ignore all other deservers described in the Quran on which Zakat can be spent. Zakat seeking organizations run extensive campaigns during the month. Quick-relief providing organizations use more appeals than organizations working on longer projects. Keywords: Zakat, Pakistani national newspapers, religious advertisements, Media Exposure, CDA, Persuasion, appeals